Performance of Gladiolus Cultivars on Morphological Traits and Corm Production under the Agro-Climatic Conditions of Peshawar-Pakistan - Nasir, Shahab; Ahmad, Masood; Ali, Hamza; Jabin, Shahana; Khan, Achak; Midrar Ullah; Bano, Arifa; Khan, Hamza Ahmad; Khan, Abbas; Arif Ullah (Indus Journal of Bioscience Research, 2025)
Gladiolus is an important commercial cut flower valued for its vibrant colors and spikes with extended vase life. However, the growth and corm production of different cultivars are highly affected by environmental factors. In areas like Peshawar-Pakistan, limited research exists to guide the selection of suitable gladiolus cultivars that can thrive under these conditions. Inadequate knowledge about the adaptability and performance of available cultivars often results in weak growth, late flowering, and low production of corms, making it a challenge for commercial production. In this regard, an experiment was designed on the Performance of gladiolus cultivars on morphological traits and corm production under the agro-climatic condition of Peshawar was conducted at Ornamental Nursery, Department of Horticulture, The University of Agriculture Peshawar. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Three cultivars of Gladiolus viz., namely White Prosperity, Rose Supreme and Magma were used for their performance. Significant variation (P≤0.05) was recorded among cultivars regarding morphological traits and corm production. The cultivar White Prosperity took minimum days to emergence (8.33 days), having maximum plant height (102 cm) and produced maximum number of leaves plant-1 (8), number of florets spike-1 (13), number of cormels corm-1 (20) and daughter corm weight (17.6 g) compared to Rose Supreme and Magma. It is concluded that the cultivar White Prosperity is recommended for quality flower and corm production under the agro-climatic condition of Peshawar valley.